The Effect of adding (Dodecyl Benzene Ammonium Sulphonate) on the Compressive Strength Properties of the Cement. - A. hamadi, Hameed; S. Abed, Dawood; K. Hussain, Haleem; A.A. ABbud, Muthanna; H. Malic, Fatemia (University of Thi-Qar Journal of Science, 2009)
We studied the effect of adding (Dodecyl Benzene Ammonium Sulphonate) as afunction ofdifferent ratio( 1% - 8%) where these additives added to the matrix of Iraqi cement (Om Quasarfactory for cement) .All the prepared samples were in form of cubic with aside ( 50 mm ) long andevaluated as afunction of dipping time in distilled water . All the prepared samples had a proportionof cement to sand ). The obtained results showed that the (Dodecyl Benzene Ammonium Sulphonate) tends to decrease the compressive strength of the modified cement mixture withincreasing curing time with distilled water where the amount of decrease linearly when curing time is21 days but less decrease in compressive strength obtained when curing time is 3 and 7 days whilethe relative compressive strength decrease linearly also as a function of adding ratio when curing timeis 3 days. Also surfactant (Dodecyl Benzene Ammonium Sulphonate) acting as plasticizer on cementmatrix leading to flexible cement. Finally the obtained results showed that there is a critical ratio of (Dodecyl Benzene Ammonium Sulphonate) depending on the kind of used cement and curingconditions enabling us to use this modified cement in many application specially in industrial and oilfor the high workability of this cement and the less water needs.